Combined zinc and vitamin B6 deficiency in a patient with diffuse red rash and angular cheilitis 6 years after Roux-en-Y gastric bypass. Issue 8 (2nd August 2019) - Freitas, Jared; Bliven, Patrick; Case, Robert
Abstract : A 39-year-old woman with a history of Roux-en-Y gastric bypass (RYGB) surgery and alcohol use presented with a confluent erythematous rash involving the perineum spreading outward to the abdomen, thighs and lower back. She had angular cheilitis and glossitis. The rash was painful and blistering in scattered areas. She was hypotensive and appeared to be in septic or hypovolemic shock at presentation. Serum levels of zinc and vitamin B6 were critically low and biopsy of her rash returned suggestive of a nutritional deficiency as its source. The rash slowly improved over the following 2 weeks with oral zinc and vitamin B6 replacement. The body rash resembled that of infants born with inherited defects in zinc transporters, referred to as acrodermatitis enteropathica (AE). This case may represent an acquired case of AE in the setting of prior RYGB.